On the linkages between exchange rate movements stock, bond and interest rate market in a regime-switching model: Evidence for Asean and East Asia - Kongliang Zhu (2018)
© 2016 by the Mathematical Association of Thailand. All rights reserved. This study analyzes the relationship among exchange rate (against US dollar), interest rate, government bond and the stock market in three ASEAN countries consisting of Thailand, Malaysia, Singapore and three East Asia countries comprising Japan, Korea, and China. The paper analyzes the question whether there exist a correlation between these variables in both high growth and low growth economy and whether there exist a similar market pattern in these countries. In this study, we estimate the correlations between these variables using the MS-VECM approach. In addition, the obtained regime probabilities allow us to detect and identify the factor or event affecting the movement of the financial markets.